Quantification of hydration products in rice husk ash (RHA)-blended cement concrete with crumb waste rubber tires (CWRT) & its correlation with mechanical performance - David, John Mark L. (Animo Repository, 2021)
Previous researches on the utilization of rice husk ash (RHA) as a replacement of cement has focused on attributing the strength enhancements in mechanical strength in hardened concrete to its pozzolanic reactivity. Investigation of the pozzolanic reaction RHA in terms of cement hydration has yet to be examined. Therefore, this study intended to assess the pozzolanic activity of RHA by quantification of calcium hydroxide (Ca(OH)2 or CH) and calcium silicate hydrate (C-S-H) gel in pure and RHA-blended cement pastes using simultaneous thermogravimetric and differential-thermal analysis (TG-DTA). Moreover, the application of crumb waste rubber tire (CWRT) in concrete as fine aggregate replacement is generally known to reduce mechanical strength. Thus, the pozzolanic reaction of RHA compensating the strength loss by CWRT was also investigated. Two types of RHA, from open-air burning (RHA-O), and thermal power plant (RHA-T), were used in casting cement pastes and mortars with 7.5%, 12.5%, and 17.5% replacement of cement by RHA. Finally, concrete with both fixed optimal RHA and 5%, 10%, and 15% CWRT were tested for compression and splitting tensile strength. TG-DTA results revealed reductions in quantified CH contents and an increase in C-S-H gel contents in cement pastes with RHA indicating pozzolanic reaction. It was also observed that decreasing CH content corresponds to increasing compressive strength highlighting the strength enhancement by pozzolanic activity, optimal at 17.5% using RHA-O. For concrete, results showed that concrete with 17.5% RHA-O and 5% CWRT was cost-efficient and provided comparable compressive strength and higher splitting tensile strength comparable to normal concrete, signifying the compensation of strength loss of CWRT by RHA.